Typographic Design in the Digital Studio - Amdur, David A. (Thomson/Delmar Learning, 2007)
In this two-book set, each lesson in typography is paired with a companion lesson in a sequenced introduction to the digital tools of design production. This combination allows the student to put theory directly into practice